Novel strategies to improve shelf-life and quality of foods : quality, safety, and health aspects - Mishra, Santosh K.; Goyal, Megh Raj (Palm Bay, FL, USA ; Burlington, ON, Canada : Apple Academic Press ; Boca Raton, FL USA ; Abingdon, Oxon, UK : CRC Press, 2021)
"This volume focuses on food preservation prior to distribution and sale, which is a major challenge in the tropical climates of most developing nations. In order to assure that food products are safe for human consumption, due importance must be given to the quality and safety aspects of production, processing, and distribution. This volume provides an informative overview of recent research on the therapeutic potential of various new and natural compounds along with novel technologies for enhanced shelf-life longevity and food safety. It also looks at the antimicrobial constituents of different sources and the history of their use as biopreservatives. It includes scientific evaluations of their use as alternative or potential biopreservatives. Focusing on real-life applications in consumer and food products, the book is divided into three parts, covering health and quality aspects of food preservation, applications of novel biomolecules for quality and safety of foods, and novel research techniques in food biopreservation. Key features: Discusses traditional natural compounds and modern technologies to reduce the spoilage of food products, looks at the therapeutics and their mechanism of actions of biological compounds for food safety, reports on new developments and novel strategies for food safety and quality improvement. Novel Strategies to Improve Shelf-Life and Quality of Foods: Quality, Safety, and Health Aspects will be a useful reference for faculty and advanced students in food science as well as for food industry quality practitioners and other industry professionals in the food and dairy industries."--
Preservation of Bovine Colostrum: Immunotherapeutic Agents to Promote Health / Krishan K. Mishra -- Essential Oil-Based Combined Processing Methods to Pursue Safer Foods / Manju Gaare, Shaik Abdul Hussain, and Santosh K. Mishra -- Potential Use of Herbs in Milk and Milk Products / Pravin D. Sawale, Writdhama Prasad, Shaik Abdul Hussain, Veena Nagarajappa, and Santosh K. Mishra -- Antifungal Lactic Acid Bacteria (LAB): Potential Use in Food Systems / Saurabh Kadyan and Diwas Pradhan -- Applications of Antimicrobial Enzymes in Foods / Veena Nagarajappa, Pravin D. Sawale, Surendra N. Battula, and Venus Bansal -- Health Benefits of Antimicrobial Peptides / Sunita Meena, Kapil Singh Narayan, and Sandeep Kumar -- Applications of Bdellovibrio Bacteria as a Biocontrol Agent Food Safety and Mitigating Clinical Pathogens / Valerie D. Zaffran, Gabrielle Kirshteyn, and Prashant Singh -- Safety Aspects of Novel Bacteriocins / Tejinder P. Singh and Shalini Arora -- Potential of Nonthermal Plasma Technology in Food Preservation / Sujit Das and Subrota Hati -- Potential of High Hydrostatic Pressure Technology in Food Preservation and Food Safety / Rekha Chawla, Venus Bansal, S. Sivakumar, Narender K. Chandla, and Santosh K. Mishra -- Application of Pulsed Light Technology in Microbial Safety and Food Preservation / Venus Bansal, Narender K. Chandla, Rekha Chawla, Veena Nagarajappa, and Santosh K. Mishra -- Novel Packaging Systems for Food Preservation / Narender K. Chandla, Venus Bansal, Gopika Talwar, Santosh K. Mishra, and Sunil K. Khatkar -- Role of Biosensors in Quality and Safety of Dairy Foods / H.V. Raghu, Ajeet Singh, and Naresh Kumar -- Potential Use of Lactic Acid Bacteria (LAB): Protective Culturesin Food Biopreservation / Manju Gaare and Santosh K. Mishra.
OCLC-licensed vendor bibliographic record.
Keywords: Food -- Preservation; Food -- Quality; Food -- Biotechnology; SCIENCE / General; TECHNOLOGY / Food Science